Pengaruh Digitalisasi dan Perilaku Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi Karyawan PT. BNI (Persero)Tbk Divisi Retail Collection & Recovery di Jakarta Tahun 2023 - Syadat, Fahrul Anwar; Irwansyah, Irwansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The objective of this study is to find out and analyze the influence of digitalization on the level of compliance of individual taxpayers and the behavior of taxpayers on the level of compliance of individual taxpayers and to know how much the influence of digitalization and the behavior of taxpayers have on the level of compliance of individual taxpayers at PT Bank Negara Indonesia (Persero) Tbk. Retail Collection & Recovery Division in 2023. The conclusion of this study identified that the digitalization has an effect on taxpayer compliance. The better quality and modem in the tax reporting system will make it easier for taxpayers to carry out their obligations, this is because it is more efficient, faster, easier and can be done anywhere. Taxpayer behavior upon individual taxpayer compliance, poor awareness and knowledge of the importance of tax reporting as an internal factor and the influence of the environment around the taxpayer as an external factor. It is identified that digitalization and taxpayer behavior have an influence on taxpayer compliance because of awareness and technological developments in tax reporting so that it is easier for people to report taxes.